2015
DOI: 10.4306/pi.2015.12.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Stress Changes the Spatial Arrangement of Neurons and Glial Cells of Medial Prefrontal Cortex and Sertraline and Curcumin Prevent It

Abstract: ObjectiveThe present study explored the three-dimensional spatial arrangements of the neurons and glial cells within the medial prefrontal cortex (mPFC) of rats.MethodsIt evaluated the arrangement for differences after stress with or without treatment with curcumin and sertraline using second-order stereology. Orientator method was applied to obtain isotropic uniform random sections of mPFC. The pair correlation g(r) and cross-correlation functions were estimated by counting dipole probes superimposed on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our previous study revealed a difference in the neurons and glial cells spatial patterns in medial prefrontal cortex after chronic stress. Interesting data on structural changes that cannot be detected only by qualitative analysis can be obtained by evaluation of the spatial arrangement [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed a difference in the neurons and glial cells spatial patterns in medial prefrontal cortex after chronic stress. Interesting data on structural changes that cannot be detected only by qualitative analysis can be obtained by evaluation of the spatial arrangement [18].…”
Section: Discussionmentioning
confidence: 99%
“…2). The covariance of a component (X) was estimated by the following equation [18]: C(r) X = SDP (X, r)/SDP (ref, r), where DP(X, r) and DP (ref, r) are the dipole length which hit the favoured structure and the nervous tissue. Pair correlation function is the normalised covariance function obtained by dividing covariance by the reference value (squared volume fraction) [18]: g(r) = C(r)/Vv2.…”
Section: Estimations Of Covariance and Pair Correlation Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheral nerve injuries (sciatic nerve) were induced in rat models and co-treatment of curcumin in these conditions assessed (Noorafshan et al, 2011[ 13 ][ 14 ]). Since emotional stress are the indispensable parts of life, the next evaluations were arranged to show whether curcumin could improve behavioural and structural changes of the brain after induction of stress and depression models (Noorafshan et al, 2013[ 6 ], 2014[ 4 ], 2015[ 7 ][ 5 ]). The preservative agents and artificial dyes are used commonly in food and drug industries, and their adverse impacts on the mammalian bodies have been approved.…”
Section: mentioning
confidence: 99%
“…Estimation of covariance "C(r)" and pair-correlation functions "g(r)" is one of these techniques to explore the three-dimensional arrangements of cell-cell or organelle-organelle. This method has been applied in estimation of the spatial allocation of a variety of histological particles including histological components of the benign and malignant prostatic tissues, microstructures of the diabetic heart, the A-cell and B-cells of dorsal root ganglion, the neuron-glia of the frontal cortex of the stressed rats, and the sub cellular localization of the organelles in the acinar cells of salivary gland [3][4][5][6][7]. Here, the C(r) and g(r) have illustrated spatial arrangement of the particles in the histological tissue samples.…”
mentioning
confidence: 99%